Accounting Treatment of Accounts Receivable and its Effect on Financial Statements and Account Receivables Collectability at The Royal Santrian Luxury Beach Villas - N P Meliawati; I M Ariana; I G M Karma (Journal of Applied Sciences in Accounting, Finance, and Tax, 2019)
The Royal Santrian Luxury Beach Villas applies a credit policy in their operations. The credit policy applied by the company must get more attention then cash sales because it will generate receivables. The Financial Accounting Standard states that a company needs to determine the interpretation of accounts with the aim of disclosure of financial statements can have a positive impact on the feasibility of financial statements, both for companies and parties outside the company. The analysis technique used in this study is a comparative descriptive analysis technique with quantitative discussion. The results of the study indicate that overall financial reporting applied by the company has not been in accordance with financial accounting standards and has an effect on the financial statements as well as an assessment of the collectibility of accounts receivable. In the financial statement there is an additional account for allowance for bad debt so that will reduce the value of the asset, and a decrease in the value of profit for the period. In the income statement, there is the addition of bad debt expense so that there is an increase in operating costs and a decrease in profit. The assessment of the collectibility of accounts receivable from the results of the ratio analysis looks less good. This means that with a non-conformity in the accounting treatment of accounts receivable, it can provide wrong information about the financial statements.